The Role of Social Workers in Assisting and Empowering the Social Welfare of Vulnerable Communities - Patricio Contreras (International Journal of Taklimat Science Review, 2026)
Social work plays a crucial role in addressing social disparities and improving the social functioning of vulnerable communities. However, the effectiveness of social worker interventions is often hampered by limited access to resources and social stigma. This study aims to analyze in-depth the implementation of social workers' roles (as enablers, mediators, counselors, and advocates) in assisting and empowering vulnerable communities, and to identify supporting and inhibiting factors in this process. The research method used was descriptive qualitative with a case study approach. The results showed that interventions conducted through casework and groupwork methods successfully increased the client's psychosocial independence index by 75%. The roles of enabler and counselor proved most effective in healing trauma and improving client self-esteem in the initial stages of intervention. Meanwhile, the roles of mediator and advocate successfully opened access to health insurance, legal aid, and job training that were previously difficult for vulnerable communities. The main obstacles encountered in the field included limited institutional operational budgets, sectoral egos between agencies, and a lack of public understanding of the regulations of Law No. 14 of 2019 concerning Social Work. This study concludes that strengthening the competency of certified social workers and cross-sectoral synergy are key to the sustainability of empowerment programs. The practical implications of this research emphasize the need for improved budgeting policies by local governments to support the operationalization of social work practices at the grassroots level.